Validity of the QuizWhizzer-Based Assessment Instrument for Measuring Middle School Students' Multirepresentation Ability - Putri, Amelia Eka; Nuha, Ulin; Mahardika, I Ketut (Peneliti.net, 2024)
Science learning at school provides benefits for students. Students can immerse themselves in nature in solving real-life problems using the multi-representational abilities that have been applied in learning. Multirepresentation ability is the ability to re-represent the same concept in different formats in physics concepts. Teachers have an important role in learning activities at school. Teachers are required to always think creatively, be innovative, and have the ability to invite students to play an active role in classroom learning. One assessment instrument (test) that can be used is QuizWhizzer. QuizWhizzer is a game that can be used in learning, with the aim of making students feel happy and not bored while learning, as well as helping teachers present material that is more interesting and not boring. QuizWhizzer is used as a medium for testing an assessment instrument. Assessment instruments have an important role in learning, namely to find out how high students' understanding of the material is. The assessment instrument consists of one aspect, namely valid. The instrument can be tested if it has passed the validation stage by the validator. If the instrument has been said to be valid then it can be tested on students.